THE EFFECT OF VILLAGE APPARATUS COMPETENCE, INTERNAL CONTROL SYSTEM, AND ORGANIZATIONAL COMMITMENTS ON VILLAGE FUND MANAGEMENT ACCOUNTABILITY (Case Research in Banyudono District) - Laidestifre Santoso; Suprihati Suprihati; Suhesti Ningsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The research purposes were 1) determined the effect of the competence of village government officials on the accountability of village fund management in Banyudono District; 2) determined the effect of the Internal Control System on the accountability of village fund management in Banyudono District; and 3) determined the effect of organizational commitment on the accountability of village fund management in Banyudono District. The research type is quantitative research. The research population is employees who work in 15 village offices in the Banyudono district. The research sample was 75 people with purposive sampling technique. The dependent variable is the accountability of village fund management. The independent variables are the competence of village government officials, internal control systems, and organizational commitment. The data analysis method used Multiple Linear Regression using SPSS test equipment. The research results can be concluded that 1) the competence of village government apparatus has a positive and significant effect on the accountability of village fund management. 2) The internal control system has no significant effect on the accountability of village fund management. 3) Organizational commitment has a positive and significant effect on the accountability of village fund management. 4) Competence of Village Government Apparatus, Internal Control System, and Organizational Commitment are able to determine the accountability of village fund management by 61.0%, the remaining 39.0% is explained by other factors not explained in the regression model. Keywords: Competence of Village Government Apparatus, Internal Control System, Organizational Commitment, Accountability of Village Fund Management